Torreya grandis nut peptides regulate lipid-II inhibitors in high-fat diet-fed mice - Rabia Durrani; Sun Yutian; Hou Bowen; Hammad Ullah; Erwann Durand; Yang Meiyun; Long Yiyang; André Delavault; Muhammad Yasir; Huan Weiwei; Gao Fei; Song Lili (Food Chemistry: Molecular Sciences, 2025)
Plant-derived bioactive peptides have drawn increasing attention in the field of nutrition and food science due to their biological activities, low cost, safety, and ease of industrial production. Functional peptides from Torreya grandis are being investigated due to their potential as dietary supplements. This study focuses on T. grandis nut peptides that regulate LIPID-II inhibitor in mice fed a high-fat diet. Proteome analysis identified a Vicilin-like antimicrobial peptide involved in host defense. 16S rRNA Sequencing revealed alteration in gut microbiota with T. grandis administration as manifested by increased Akkermansia and Parabacteroides concurrently by decreased Firmicutes. Beneficial bacteria i.e., Akkermansia improved intestinal functions and increased levels of short chain fatty acids (SCFAs). T. grandis supplementation in HFD mice reduced body weight, TC, TG, LDL, and decreased inflammation, while reducing oxidative stress and increasing HDL in the model group fed a high-fat diet. Lipid droplets in liver, muscles, and blood vessels were highly reduced, evoked by the high peptide group. Transcriptome analysis highlighted lipid regulation via the PPAR-α pathway, with molecular docking revealing 4 potential lipid II inhibitory peptides. These findings suggested T. grandis as a promising supplement in food and a key nut for nutraceutical purposes.